PERAN GEREJA DALAM BIMBINGAN PRANIKAH DAN PENDAMPINGAN PASANGAN SUAMI ISTRI PASCA MENIKAH - Tju Lie Lie; Wegi Oktariadi (The Way Jurnal Teologi dan Kependidikan, 2019)
The purpose of this thesis research includes; Convey to each reader the views of Christian Marriage in accordance with the Bible; Provide an overview of how Prenuptial Guidance Services (BPN is effective and appropriate for marriage preparation; Provide an overview of the importance of the Role of the Church through BPN. The method used by the author in this study is library research. The excavation of the Bible is the main and basic source of every thought pattern, and conduct field research in order to obtain accurate information and facts that can support the writing of scientific work. The involvement of the church is very important. How God really missed the family fulfilling the divine purpose on earth, then it should a marriage is prepared as well as possible so that each couple is able to enter their marriage with the right understanding and purpose.The results of the research that the author gets, namely: The involvement of BPN is ameans for every premarital couple to learn about family life; effective BPN involvement when early debriefing for each pair is to know basic values that contain Bible truths; Produce quality "Christian families". The conclusions of this study are as follows; Christian marriage is God's representative. Premarital guidance (BPN) is a ministry in the church that provides guidance on how to build a quality Christian family. BPN should be a continuous service with other services. Advanced BPN to equip every couple who has entered marriage. With effective BPN services, it is expected to produce quality Christian families.